Measuring customers satisfaction: a case study at Bintulu Development Authority (BDA)/ Abg Mohd Tahir Abg Masagus - Abg Masagus, Abg Mohd Tahir (2006)
Determining customer satisfaction is fundamental to effective delivery of services in the Public Sector. Successfully being able to judge customers’ satisfaction levels and to apply that knowledge potentially gives an advantage over competitors or other organisations. Given a vital role of customers satisfaction, one should to be surprised that a great deal of research has been devoted to investigating the process by which customers form judgments about a service experience.